Awareness and prevalence of diabetic retinopathy among diabetic patients attending Dailekh District Hospital, Karnali Province, Nepal - Panta, Niranjan; Joshi, Omprakash; Basnet, Lila Bahadur (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Diabetic retinopathy is the leading cause of blindness worldwide in the age group 20-64 years. Awareness plays crucial role in management and prevention of this serious complication. There is a need of assessment of the awareness level and prevalence of diabetic retinopathy among diabetic patients in Nepal, especially in rural community. This study was intended with an objective to find out the awareness status and prevalence of diabetes retinopathy. Method: A cross-sectional study was carried among the patients visiting a district hospital. The district was chosen by purposeful sampling. A total of 236 required sample size was met by convenience sampling technique and asked to fill out the questionnaire prepared in Nepali to assess awareness of diabetic retinopathy. Detailed ophthalmologic consultations of the patients were done. Result: Most of the patients' knowledge about DR inferred from treating physicians and other means of awareness from media and family members. About twenty-four percent of respondents had a good awareness of DR. Awareness was better in males which was statistically significant at p-value of <0.013. All the respondents pointed to lack of visual symptoms as the biggest factor for not getting an eye examination. Twenty-seven percent of respondents who returned with ophthalmic consultation had some form of DR. Conclusion: Overall awareness of DR was poor in this study. No one had met diabetic educators at any point of treatment which should be emphasized for the management of diabetes mellitus. Also, the role of media is equally important to spread awareness of DR.